Effect of Low Temperature Pre-annealing on Oxygen Related Donors Formation in N-Doped CZ-Silicon - Dubey*, Vikash (Recent Research in Science and Technology, 2011)
<span style="font-size: 10pt; font-family: ";Arial Narrow";,";sans-serif";; mso-ansi-language: EN-US; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: 'Times New Roman'; mso-bidi-language: AR-SA; mso-fareast-language: EN-US;">In view of the interesting informations revealed by the studies of nitrogen in silicon, an attempt has been made to look into the behaviour of low temperature pre-annealing at 4800C for shorter duration of 10 h and longer duration of 40 h in N-doped CZ-Si annealed at 6500C up to 90 h by subjecting the samples to two basic characterizing tools. Low temperature pre-annealing for a shorter duration followed by annealing at 6500C does not register an increase in donor concentration, while reverse is true for pre-annealing of 40 h. Longer pre-annealing time at low temperature brings about a larger increase in the donor concentration during the annealing. Donors generated in N-undoped CZ-Si samples never attain saturation up to 90 h of annealing at 6500C, while in N-doped silicon annealed for 60 h, the donors generated reached a saturation stage and no change is observed by annealing for longer duration.